Evaluating the life cycle energy benefits of energy efficiency regulations for buildings - Crawford, Robert H.; Bartak, Erika L.; Stephan, André; Jensen, Christopher A. (Renewable & sustainable energy reviews, 2016)
Energy efficiency regulations for buildings often focus solely on operational and thermal energy demands. Increasing a building׳s thermal energy efficiency is most often undertaken by increasing insulation thickness and installing high performance windows. These measures can result in a significant increase in embodied energy which is currently not considered in the majority of existing building energy regulations. This study uses a case study house in Melbourne and Brisbane, Australia to investigate the life cycle primary energy repercussions of increasing building energy efficiency levels over 50 years. It uses the comprehensive hybrid approach and a dynamic software tool to quantify embodied and operational energy, respectively. It considers material and design-related changes in order to improve energy efficiency as well as a combination of both. Results show that while increasing the envelope thermal energy performance yields thermal operational energy savings, these can be offset by the additional embodied energy required for supplementary insulation materials and thermally efficient windows. The point at which supplementary insulation materials do not yield life cycle energy benefits is just above current minimum energy efficiency requirements in Australia. In order to reduce a building׳s life cycle energy demand, more comprehensive regulations are needed. These should combine embodied and operational energy and emphasise design strategies.